Developing Fine Motor Skills in Early Childhood through Finger Painting Activities - Tsamrotul Fuadah; Rukiyah Rukiyah; Lia Dwi Ayu Pagarwati (Universitas Sebelas Maret, 2026)
Fine motor skill development is a crucial aspect of early childhood development that needs to be stimulated through engaging learning activities tailored to children’s characteristics. One activity that can be used to stimulate fine motor skills is finger painting, as it directly involves the coordination of finger, hand, and eye movements. This study aims to examine the fine motor development of young children through finger painting activities. The study employs a qualitative approach with a descriptive design. The research subjects consisted of 16 children aged 4–5 years. Data collection techniques included observation, interviews, and documentation, while data analysis utilized the Miles and Huberman model. The results of the study indicate that finger painting activities can improve eye-hand coordination, finger flexibility, and children’s movement control during the activity. Additionally, this activity also enhances children’s creativity, self-confidence, and active participation in learning. Thus, finger painting can serve as an effective and innovative learning strategy for developing the fine motor skills of young children.